Role of Microfinance Services on Enhancing Quality of Life of Women in Pokhara Metropolitan City - Ojha, Deepak; Dhungana, Bharat Ram; Ranabhat, Deepesh; Adhikari, Sujita; Adhikari, Rina (Journal of Interdisciplinary Studies, 2025)
Microfinance services including savings, insurance, remittance, and microcredit primarily target women, empowering them to generate income, create assets, and achieve greater financial independence. This study examines the role of microfinance in fostering the quality of life of female clients with a specific focus on microfinance institutions in Pokhara metropolitan, Kaski, Nepal. A sample of 171 respondents was selected from unknown population using a convenience sampling method. Data were collected through structured questionnaires and analyzed using descriptive statistics, correlation, and linear regression techniques. The findings reveal that microfinance significantly improves the economic status of women by enabling them to start small businesses, increase savings, and enhance consumption. Among the different dimensions, financial literacy and micro-enterprise development emerged as the most influential factors, showing significant positive effects on quality of life. While microcredit contributes modestly, micro-insurance demonstrates a weaker influence, suggesting limited perceived benefi ts. Overall, microfinance initiatives strengthen financial capabilities but only moderately translate into improved quality of life, indicating the need for more comprehensive and targeted interventions. The results underscore the importance of microfinance in driving societal and national development, offering valuable insights for policymakers and stakeholders in microfinance institutions (MFIs).